Effect of muncipal garbage on the growth and vigour of rose wood (Dalbergia latifolia Roxb) seedlings in the nursery - Sreelekha P T (Department of Tree Physiology and Breeding, College of Forestry, 2004)
The present study to evaluate the effect of potting media containing fresh and decomposed municipal garbage on the growth and vigour of rose wood (Dalbergia latifolia Roxb.) seedlings in the nursery was carried out at the College of Forestry, Kerala Agricultural University, Vellanikkara, Thrissur during the period 2002-2004. A total of twelve treatments with and without municipal garbage were tried for raising the seedlings. . The result of the study revealed that seedlings could not be established when fresh municipal garbage alone was used as potting media. The potting medium containing soil: 4 weeks decomposed municipal garbage recorded the maximum height, where as maximum collar diameter was observed when the seedlings were grown in medium containing soil: sand: cowdung in equal proportions. This medium was also found to be superior with regard to shoot fresh and dry weights.